Use of energy-filtered photoelectron emission microscopy and Kelvin probe force microscopy to visualise work function changes on diamond thin films terminated with oxygen and lithium mono-layers for thermionic energy conversion. (1st January 2014) - Andrade, H.D.; Othman, M.Z.; O'Donnell, K.M.; Lay, J.H.; May, P.W.; Fox, N.A.; Morin, J.; Renault, O.
Kelvin probe force microscopy (KPFM) and energy-filtered photoelectron emission microscopy (EF-PEEM) with vacuum UV (VUV) excitation have been used to study the work function of p -type diamond films treated to exhibit a negative electron affinity (NEA) surface. NEA was generated by a lithium-oxygen monolayer termination. This monolayer was achieved in two different ways: thermally evaporated films 50 nm thick were either treated by in situ vacuum annealing or by a subsequent water wash. The work function values obtained from these samples by EF-PEEM were compared with KPFM measurements to establish which of the two fabrication techniques was most effective in activating a NEA surface. The washing method was shown to be more effective and the work function values obtained by the two techniques were comparable, as they showed the same work function peaks at 4.54 eV in their respective histograms. It was found that neighbouring polycrystalline facets could show a large variation in work function of up to 400 meV.